Effect of Acidizing Process on the Stress Corrosion Cracking of HP-13Cr Stainless Steel in the Ultra-depth Well Environment - Qi, Wenlong; Zhao, Yang; Zhang, Tao; Wang, Fuhui (Frontiers in Materials, 2021)
The effect of acidizing process on the stress corrosion cracking of HP-13Cr stainless steel in the ultra-depth well environment was studied by the slow strain rate test, the electrochemical measurement, the microstructure observation and the finite element modeling. The results indicated that the acidizing process significantly increased the stress corrosion cracking susceptibility of HP-13Cr stainless steel and induced the fracture mode to the brittle characteristic in the high temperature and CO2 pressure environment. The stress corrosion cracking susceptibility also increased with the increasing of temperature and CO2 pressure. There were dense defects including pits and cracks in the fracture section from the transverse view. After acidizing process, under tensile stress condition, the increasing roughness will cause the stress concentration and promoted the local anodic dissolution, which inducing the initiation of stress corrosion cracking.